Grape seed proanthocyanidins inhibit the invasive potential of head and neck cutaneous squamous cell carcinoma cells by targeting EGFR expression and epithelial-to-mesenchymal transition - Sun Qian; Prasad Ram; Rosenthal Eben; Katiyar Santosh K (BMC, 2011)
Abstract Background Head and neck squamous cell carcinoma (HNSCC) is responsible for over 20,000 deaths every year in United States. Most of the deaths are due, in large part, to its propensity to metastasize. We have examined the effect of bioactive component grape seed proanthocyanidins (GSPs) on human cutaneous HNSCC cell invasion and the molecular mechanisms underlying these effects using SCC13 cell line as an in vitro model. Methods The therapeutic effects of GSPs on cancer cell invasion were studied using Boyden chamber and wound healing assays. The effects of GSPs on the levels of various proteins related with cancer cell invasion were determined using western blot analysis. Results Using in vitro cell invasion assays, we observed that treatment of SCC13 cells with GSPs resulted in a concentration-dependent inhibition of cell invasion of these cells, which was associated with a reduction in the levels of epidermal growth factor receptor (EGFR). Treatment of cells with gefitinib and erlotinib, inhibitors of EGFR, or transient transfection of SCC13 cells with EGFR small interfering RNA, also inhibited invasion of these cells. The inhibition of cell invasion by GSPs was associated with the inhibition of the phosphorylation of ERK1/2, a member of mitogen-activated protein kinase family. Treatment of cells with UO126, an inhibitor of MEK, also inhibited the invasion potential of SCC13 cells. Additionally, inhibition of human cutaneous HNSCC cell invasion by GSPs was associated with reversal of epithelial-to-mesenchymal transition (EMT) process, which resulted in an increase in the levels of epithelial biomarker (E-cadherin) while loss of mesenchymal biomarkers (vimentin, fibronectin and N-cadherin) in cells. Similar effect on EMT biomarkers was also observed when cells were treated with erlotinib. Conclusion The results obtained from this study indicate that grape seed proanthocyanidins have the ability to inhibit the invasion of human cutaneous HNSCC cells by targeting the EGFR expression and reversing the process of epithelial-to-mesenchymal transition. These data suggest that GSPs can be developed as a complementary and alternative medicine for the prevention of invasion/metastasis of HNSCC cells.